The First 90 Days - Watkins, Michael (Ascent Audio, 2013)
The world's most trusted guide for leaders in transition Transitions are a critical time for leaders. In fact, most agree that moving into a new role is the biggest challenge a manager will face. While transitions offer a chance to start fresh and make needed changes in an organization, they also place leaders in a position of acute vulnerability. Missteps made during the crucial first three months in a new role can jeopardize or even derail your success. In this updated and expanded version of the international bestseller The First 90 Days, Michael D. Watkins offers proven strategies for conquering the challenges of transitions-no matter where you are in your career. Watkins, a noted expert on leadership transitions and adviser to senior leaders in all types of organizations, also addresses today's increasingly demanding professional landscape, where managers face not only more frequent transitions but also steeper expectations once they step into their new jobs. By walking you through every aspect of the transition scenario, Watkins identifies the most common pitfalls new leaders encounter and provides the tools and strategies you need to avoid them. You'll learn how to secure critical early wins, an important first step in establishing yourself in your new role. Each chapter also includes checklists, practical tools, and self-assessments to help you assimilate key lessons and apply them to your own situation. Whether you're starting a new job, being promoted from within, embarking on an overseas assignment, or being tapped as CEO, how you manage your transition will determine whether you succeed or fail. Use this book as your trusted guide.